Families in economically hard times : experiences and coping strategies in Europe (Emerald Publishing Limited, 2019)
The purpose of the edited collection Families in Economically Hard Times: Experiences and Coping Strategies in Europe is to provide readers with unique sociological knowledge on European families' experiences and behavioural strategies a decade after economic crisis of the 21st century. The particular importance of the topic is conditioned by the reality the last economic crisis created. This new reality has diverted from the previous; and as new phenomena emerge new coping strategies must also be created, as the old may not necessarily work. Hardships, functional solidarity, and issues of vital human needs - including practices of co-residence, sharing of money, food acquisition - have been explored in Families in Economically Hard Times: Experiences and Coping Strategies in Europe. Prominent scholars from Europe have joined efforts and, based on their latest researches, seek to answer the question: how challenges emerged during recent economically hard times influenced way of life of European families? The scholars of this book have used quantitative and qualitative research methodologies to create a varied and all rounded approach to answering this very question.